Strange cocktail : translation and the making of modern Hebrew poetry - Jacobs, Adriana Ximena, 1976- (Michigan studies in comparative Jewish cultures., 2018)
For centuries, poets have turned to translation for creative inspiration. Through and in translation, poets have introduced new poetic styles, languages, and forms into their own writing, sometimes changing the course of literary history in the process. Strange Cocktail is the first comprehensive study of this phenomenon in modern Hebrew literature of the late nineteenth century to the present day. Its chapters on Esther Raab, Leah Goldberg, Avot Yeshurun, and Harold Schimmel offer close readings that examine the distinct poetics of translation that emerge from reciprocal practices of writing and translating. Working in a minor literary vernacular, the translation strategies that these poets employed allowed them to create and participate in transnational and multilingual poetic networks. Strange Cocktail thereby advances a comparative and multilingual reframing of modern Hebrew literature that considers how canons change and are undone when translation occupies a central position-how lines of influence and affiliation are redrawn and literary historiographies are revised when the work of translation occupies the same status as an original text, when translating and writing go hand in hand.